A new era of improving progression-free survival with dual blockade in postmenopausal HR+, HER2− advanced breast cancer. Issue 2 (February 2015) - Jerusalem, Guy; Bachelot, Thomas; Barrios, Carlos; Neven, Patrick; Di Leo, Angelo; Janni, Wolfgang; de Boer, Richard
Highlights Progression on endocrine therapy (ET) is problematic in HR+ advanced breast cancer. Targeting compensatory growth pathways may enhance or extend endocrine sensitivity. Benefits of dual targeting are most evident after disease progression on initial ET.